Evaluation of bacterial contamination in indoor swimming pools - Zahraa N.K. Al Aboudi (The Bioscan, 2025)
Background: The quality of water is a crucial factor in maintaining public health, as contaminated water can lead to the transmission of various waterborne diseases. One of the primary concerns is the contamination of swimming pools that represent a ubiquitous feature of recreational facilities particularly during the warmer months. Aim: Investigation the prevalence of bacterial contamination in water and environments of indoor swimming pools. Materials and methods: Totally, 100 swab samples were collected equally from the changing rooms, pool edges, pool ladders and water of various swimming pools in Wasit province (Iraq) during June and July (2024). Then, the swabs were cultured separately on three media (Blood Agar, Eosin Methylene Blue Agar and MacConkey Agar), purified and to identified based on their morphological characteristics and biochemical test. Results: Overall 37% of swab samples were contaminated with various species of bacteria; which found in pool edges (56%), pool ladders (44%), changing rooms (36%), and water (12%). Subsequently, the number of identified bacterial isolates was 68 (37.99%), 39 (21.79%), 45 (25.14%) and 27 (15.08%) in water, changing rooms, pool edges, and pool ladders, respectively. In changing rooms, 12 species of bacteria was reported, more significantly was Escherichia coli as well as Klepsellia aerogenes. In pool edges, 11 bacterial species were recorded; in which, significant increases were seen in Klepsellia pneumonia, Escherichia coli, as well as in Aeromonus hydrophila, and Vibrio cholera. Concerning the pool ladders, 10 bacterial species were diagnosed, particularly Vibrio cholera, Escherichia coli and Klepsellia pneumonia. Regarding water, 15 species of bacteria were recorded including Escherichia coli in addition to Vibrio cholera, Aeromonus hydrophila, Pseodomonus argenosa, Proteus mirabrillis, and less significantly in Klepsellia pneumonia, Acintopacter baumannii, Klepsellia aerogenes, Proteus vulgaris, Salmonella epidermidis, Streptococcus faecalis, Anteropacter cloacae, Citropecter frndii, Edwardsiella tarda, and Serratia liquefaciens. Conclusions: Based on results of the current study, swimming pools represent a source of various bacteria that might be transmitted to swimmer causing different infections in particular in skin. Hence, we advocated to implementation of comprehensive water quality monitoring programs and using of advanced diagnostic techniques to identify and tracking the potential pathogens with applying of effective disinfection strategies to mitigate the risk of bacterial contamination in swimming pools.